2007
DOI: 10.1038/sj.ejcn.1602831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea buckthorn berries on infections and inflammation: a double-blind, randomized, placebo-controlled trial

Abstract: Objective: To study the effect of sea buckthorn berries on the number and duration of common cold (CC) infections. As secondary objectives the effects on digestive and urinary tract infections (DTI, UTI), and serum C-reactive protein (CRP) concentrations were also investigated. Subjects: A total of 254 healthy volunteers were randomly assigned to receive sea buckthorn or placebo product during the study, which 233 of them completed. Results: There were no significant differences in the number or duration of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 41 publications
1
43
3
2
Order By: Relevance
“…It has also been shown that sea buckthorn has a positive influence on CRP (Larmo et al, 2008). However, in our study, inflammation marker hs-CRP did not change statistically significantly, although there was a slight decrease in both the groups.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…It has also been shown that sea buckthorn has a positive influence on CRP (Larmo et al, 2008). However, in our study, inflammation marker hs-CRP did not change statistically significantly, although there was a slight decrease in both the groups.…”
Section: Discussioncontrasting
confidence: 54%
“…Some indications of beneficial effects of berries and berry seed oils on serum lipid profile (Tahvonen et al, 2005), and infection marker CRP (Larmo et al, 2008) have been illustrated in human trials. However, to the best of our knowledge, this is the first human trial conducted to investigate the effects of berries on liver function and components of metabolic syndrome, although protective effects of bilberry on liver damage have been earlier postulated in an animal trial (Bao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately in human trials further positive indications have emerged. Homogenized SB berries, even at a low 28 g daily dose, have positive effects on the inflammation marker C-reactive protein in healthy normal-weight humans (Larmo et al, 2007). In a recent study, BB juice decreased C-reactive protein, interleukin (IL)-6, IL-15 and monokine, but had no effect on tumor necrosis factor (TNF)-a (Karlsen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sea buckthorn has been shown to have antiatherogenic properties (Basu et al, 2007), and to decrease oxidative stress (Suleyman et al, 2002) in animal trials. It has also been indicated to decrease the risk of coronary heart disease (Eccleston et al, 2002), prevent platelet aggregation (Johansson et al, 2000) and lower the plasma high sensitivity c-reactive protein level (Larmo et al, 2007) in human trials. Sea buckthorn and blueberry concentrate was shown to have a regenerative effect on pancreatic b cells in type 1 diabetic children (Nemes-Nagy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%